From Traditional Korean Culture to the Global Public: Reframing K-Culture through Spiritual Heritage and the Public Value of Culture - Park Kwangsoo; Thapakorn Kamnerdsiri (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2026)
Korean popular culture (K-culture) has attained exceptional global visibility under Hallyu (the Korean Wave), yet persistent critiques—commercial overreach, superficiality, and cultural insensitivity—signal limits to its appeal. This article asks what sustains K-culture’s resonance beyond platform scale and how it might address the emerging backlash. Using recent survey evidence and three foundational concepts—Cheonson (the view of humans as “Heaven’s descendants”) and Jecheon (rites venerating Heaven) and the important Mahayana Buddhist concept of Buddha-nature, which holds that all humans and living beings equally possess the potential to realize the highest state of perfection, the study theorizes how spiritual heritage can ground a shift toward public-minded cultural practice. Bringing together cultural-hybridity analysis, soft-power scholarship and its critiques, and research on emotional economies in media, the study reads K-culture as both a commercial pop industry that constitutes the nation’s economic interests and at the same time it can serve as a carrier of ethical orientations for conveying ethical concepts and values that contribute to the overall well-being of humankind. This research article argues that re-centering production and reception on universalistic values and the public value of culture can convert friction points into opportunities for dialogue, co-creation, and ethical stewardship. The proposed framework offers a concise roadmap for evolving Hallyu from a high-performing export model into a culture of hope and coexistence-globally legible yet heritage-anchored, commercially viable yet publicly accountable. K-Culture can transcend its current limitations and evolve into a “culture of hope and coexistence” that engages the global public more equitably and imaginatively.